Efficient removal of digoxin from aqueous solution using magnetic nanocomposite (Fe3O4–GO–SO3H) as an advanced nano-absorbent - Paria Pashazadeh-Panahi; Mohammad Hasanzadeh (Nanocomposites, 2020)
Digoxin separation from pharmaceuticals wastes, is small piece of the larger puzzle in holistic risk assessment. In this study, a novel magnetic nano composite (graphene oxide/Fe3O4/SO3H) was synthesized and used as an absorbent for the removal of digoxin from aqueous solution. We utilized UV-Vis spectrophotometry (UV/Vis) for detection and efficient removal of digoxin by magnetic graphene oxide (MGO) in different concentrations. Magnetic absorbent was characterized by thermal gravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). The optimized concentration of absorbent and digoxin were 500 and 1 ppm respectively, in which the optimize reaction time was lasting 10 min. Finally, under optimized condition, MGO was used for the efficient separation of digoxin from aqueous solution.